2002
DOI: 10.1177/089686080202200508
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome following Bacterial Peritonitis in Peritoneal Dialysis

Abstract: Objective No studies have been done to examine factors that predict the outcome of bacterial peritonitis during peritoneal dialysis (PD), beyond the contribution of the organism causing the peritonitis, concurrent exit-site or tunnel infection, and abdominal catastrophes. Design In this study we examined several clinical and laboratory parameters that might predict the outcome of an episode of bacterial peritonitis. Between March 1995 and July 2000, we identified 399 episodes of bacterial peritonitis in 191 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
112
5
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(141 citation statements)
references
References 26 publications
23
112
5
1
Order By: Relevance
“…The first important issue is awareness of the elevated risk for patients with long PD duration, age above 60 years, and low residual renal function, often combined with fast peritoneal transport and low nutritional indices. This is supported by our data and other reports (9,25–27). As the dialysis population grows older, and with increasing vascular and diabetic comorbidity, such patients will present increasingly more often with infectious complications (28).…”
Section: Discussionsupporting
confidence: 90%
“…The first important issue is awareness of the elevated risk for patients with long PD duration, age above 60 years, and low residual renal function, often combined with fast peritoneal transport and low nutritional indices. This is supported by our data and other reports (9,25–27). As the dialysis population grows older, and with increasing vascular and diabetic comorbidity, such patients will present increasingly more often with infectious complications (28).…”
Section: Discussionsupporting
confidence: 90%
“…Fungi accounted for 2.6% of the episodes. These percentages are similar to other long-term outcome studies (2). Of note, the rate of gram-positive peritonitis decreased significantly during the study period, but the rate of gram-negative peritonitis remained the same.…”
Section: Spectrum Of Organismssupporting
confidence: 88%
“…Krishnan et al (2) identified 399 episodes of peritonitis in order to identify factors that might predict outcome.…”
Section: Outcome Of Peritonitismentioning
confidence: 99%
“…Peritonitis causes many problems such as abdominal pain, fatigue, loss of appetite and malnutrition. [33][34][35] The QOL of dialysis patients, whether they receive HD or PD, is affected negatively by these treatment modalities. Inconsistent results were obtained in studies regarding the QOL in HD and PD patients.…”
Section: Quality Of Life In Dialysis and Related Factorsmentioning
confidence: 99%